Pelatihan Analisis Data Kuantitatif sebagai Strategi Peningkatan Keterampilan Riset ilmiah Mahasiswa - Patongai, Dian Dwi Putri Ulan Sari; Junda, Muhammad; Sartika, Dewi; Musawira; Anggita, Sri Ayu (Program Studi Manajemen FEB UNM, 2025)
The ability of students to perform quantitative data analysis is a crucial skill in conducting scientific research. However, many students face challenges, both in selecting appropriate analytical techniques relevant to their research topics and in using data analysis software such as SPSS or other supporting applications. These challenges often hinder students in analyzing research data effectively. This community service activity aims to enhance students' skills in identifying suitable analytical techniques for scientific research and in using data analysis software such as SPSS. The implementation methods include delivering materials on descriptive and inferential statistics, conducting simulations on SPSS usage, and facilitating discussion and Q&A sessions. The results of the training show an improvement in participants’ understanding of how to choose appropriate analytical techniques and operate statistical software for research purposes. This activity also contributes to increasing students’ confidence and independence in conducting scientific research. The training is expected to serve as a sustainable and integrated model for academic development in higher education institutions.